2021
DOI: 10.1111/add.15530
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption during the COVID‐19 pandemic in Europe: a large‐scale cross‐sectional study in 21 countries

Abstract: AimsTo investigate changes in alcohol consumption during the first months of the COVID-19 pandemic in Europe as well as its associations with income and experiences of distress related to the pandemic. Design Cross-sectional on-line survey conducted between 24 April and 22 July 2020. Setting Twenty-one European countries. Participants A total of 31 964 adults reporting past-year drinking. Measurements Changes in alcohol consumption

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(136 citation statements)
references
References 41 publications
5
112
1
3
Order By: Relevance
“…A recent publication by Kilian et al is in agreement with our findings and confirms a decreased alcohol consumption during the first months of the COVID-19 pandemic (23). The authors also implemented a cross-sectional on-line survey in a similar timeframe (April 24 to July 22, 2020) as our study.…”
Section: Discussionsupporting
confidence: 92%
“…A recent publication by Kilian et al is in agreement with our findings and confirms a decreased alcohol consumption during the first months of the COVID-19 pandemic (23). The authors also implemented a cross-sectional on-line survey in a similar timeframe (April 24 to July 22, 2020) as our study.…”
Section: Discussionsupporting
confidence: 92%
“…These results correspond with the findings from a large-scale, population-based study in the EU, which found that in the high-income groups an increase in alcohol use depended on the experience of financial distress. Individuals with a high income and no financial distress were more likely to decrease their alcohol use [29]. The privileged baseline of the present sample may be associated with more individual resources to cope functionally with any psychological distress that arose due to COVID-19 rather than using substances.…”
Section: Depressionmentioning
confidence: 72%
“…In contrast, a very recent study in 21 EU countries showed that in most countries, with the exception of Ireland and the United Kingdom, there was a decrease in alcohol consumption. However, a reduction in alcohol consumption was less common among people who were particularly stressed by the pandemic [29]. Other studies also found significant associations between higher levels of psychological distress, or depressive or anxiety symptoms and an increase in alcohol use.…”
Section: Introductionmentioning
confidence: 96%
“…Im Studienprotokoll [17] wurde unter "Schwächen" zwar darauf hin gewiesen, dass mit diesem Ansatz nur eine willkürliche Stichprobe zustande kommt, wobei seltsamerweise gleichzeitig unter "Stär ken" vertreten wurde, dass die Studie quantitative Aussagen er mögliche. In der Studie selbst gingen die Autoren sogar noch wei ter und vertraten die Ansicht, dass die so gewonnene Stichprobe in vielerlei Hinsicht mit den Stichproben anderer Alkoholerhebun gen in der Bevölkerung vergleichbar sei [18]. Das mag für andere Erhebungen, deren Stichproben ebenfalls hochgradig verzerrt sind, zwar zutreffen, wirkt allerdings wie eine Aufforderung an die Rezi pienten, die Studienergebnisse bedenkenlos auf die Bevölkerung zu übertragen -was aus methodologischer Sicht fraglos unzuläs sig ist.…”
Section: Introductionunclassified